Study of understanding, awareness and compliance to treatment in patients of hypertension at tertiary care center, SSG Hospital, Vadodara: a descriptive cross-sectional study - Bhudhrani, Divyang; P. Patel, Kush; P. Patel, Yashvi; J. Patel, Jinesh; S. Patel, Rudra; V. Patel, Zeel (International Journal of Research in Medical Sciences, 2025)
Background: Hypertension represents a major health issue, significantly contributing to the prevalence of cardiovascular diseases worldwide. Effective hypertension management is largely dependent on patients’ understanding, awareness, and adherence to prescribed treatments. This study aimed to assess the levels of understanding, awareness, and compliance with treatment among hypertensive patients at SSG Hospital, a tertiary care center in Vadodara. Methods: This descriptive cross-sectional study involved 300 hypertensive patients from the outpatient department of SSG Hospital, Vadodara. Data were gathered using a structured questionnaire that included demographic details, understanding about hypertension, awareness of its complications, and adherence to medications and lifestyle adjustments. Blood pressure measurements confirmed hypertension status. Statistical analyses were conducted using SPSS software to identify significant factors influencing treatment compliance. Results: Among the 427 participants, 62% demonstrated sufficient understanding of hypertension, its risk factors, and complications. Awareness was high, with 75% of patients recognizing the importance of regular medication and lifestyle changes. However, only 54% of patients were fully compliant with their treatment regimens. Higher education levels, consistent follow-up visits, and family support were significantly associated with better compliance. Conclusions: Although the majority of hypertensive patients at SSG Hospital, Vadodara, have substantial knowledge and awareness of their condition, treatment compliance remains suboptimal. Improving patient education, providing ongoing support, and addressing barriers to adherence are essential for better management of hypertension.